2019
DOI: 10.5812/jhealthscope.69158
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Sulfur Dioxide on Clinoptilolite/Nano Iron Oxide and Natural Clinoptilolite

Abstract: Background: Sulfur dioxide gas is known to include pollutants that are harmful to human health and the environment. Therefore, due to the increase of industrial activities, SO2 gas pollution control is very important. Objectives: The purpose of this study was to investigate the efficiency of sulfur dioxide removal by iron oxide nanoparticles deposited on clinoptilolite zeolite. Methods: Two materials, natural clinoptilolite and clinoptilolite containing iron oxide nanoparticles, were used as adsorbents of SO2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…The negative values of ΔG 0 at all temperatures displayed the feasibility and spontaneity of the adsorption process. Furthermore, the enhanced disorder and randomness at the solidsolution interface of Cr(VI) with the adsorbent were confirmed by the positive values of ΔS 0 [31,[45][46][47][48]. The thermodynamic and spontaneous adsorption processes between MTBs and Cr(VI) were similar to previous studies that investigated the adsorption behavior between surfactant-modified bentonite and Cr(VI) [23,24,26] (Table 1).…”
Section: Effect Of Adsorbent Weightsupporting
confidence: 84%
“…The negative values of ΔG 0 at all temperatures displayed the feasibility and spontaneity of the adsorption process. Furthermore, the enhanced disorder and randomness at the solidsolution interface of Cr(VI) with the adsorbent were confirmed by the positive values of ΔS 0 [31,[45][46][47][48]. The thermodynamic and spontaneous adsorption processes between MTBs and Cr(VI) were similar to previous studies that investigated the adsorption behavior between surfactant-modified bentonite and Cr(VI) [23,24,26] (Table 1).…”
Section: Effect Of Adsorbent Weightsupporting
confidence: 84%
“…Also, it was shown that by reducing the temperature and increasing the pressure, CO2 adsorption escalated [84]. Natural clinoptilolite and clinoptilolite containing iron oxide NPs, have been also developed for SO2 adsorption [85]. This NP was able to adsorb SO2 in synthetic and actual samples with an efficiency of 80% and 66%, respectively [85].…”
Section: Nanoadsorbentsmentioning
confidence: 99%
“…Natural clinoptilolite and clinoptilolite containing iron oxide NPs, have been also developed for SO2 adsorption [85]. This NP was able to adsorb SO2 in synthetic and actual samples with an efficiency of 80% and 66%, respectively [85]. Also, the SO2 removal percentage was calculated at 43.8 for the synthetic sample and 31.3 for the actual specimen at room temperature [85].…”
Section: Nanoadsorbentsmentioning
confidence: 99%
“…Besides these well-known sites, there are studies showing that clinoptilolite can have other cation positions containing Cs + , Ag + , Pb 2+ , Cd 2+ , Hg 2+ ions [15][16][17][18]. Clinoptilolite can be used for gas separation and removal of toxic gases due to its structural advantages [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%